Bad faith : race and the rise of the religious right - Balmer, Randall Herbert (William B. Eerdmans Publishing Company, 2021)
There is a commonly accepted story about the rise of the Religious Right in the United States. It goes like this: with righteous fury, American evangelicals entered the political arena as a unified front to fight the legality of abortion after the Supreme Court's 1973 Roe v. Wade decision. The problem is this story simply isn't true. Largely ambivalent about abortion until the late 1970s, evangelical leaders were first mobilized not by Roe v. Wade but by Green v. Connally, a lesser-known court decision in 1971 that threatened the tax-exempt status of racially discriminatory institutions--of which there were several in the world of Christian education at the time. When the most notorious of these schools, Bob Jones University, had its tax-exempt status revoked in 1976, evangelicalism was galvanized as a political force and brought into the fold of the Republican Party. Only later, when a more palatable issue was needed to cover for what was becoming an increasingly unpopular position following the civil rights era, was the moral crusade against abortion made the central issue of the movement now known as the Religious Right.